Effect of target controlled propofol infusion versus intermittent boluses during oesophagogastroduodenoscopy: a randomized controlled trial - Ndosi, Catherine (Afr Health Sci, 2019)
BACKGROUND: Propofol is administered as intermittent boluses to achieve deep sedation to facilitate oesophagogastroduodenoscopy. Target controlled infusion (TCI) can be employed for this purpose. METHODS: 176 adults were randomly allocated into two groups of 88 patients. Control group: Received an initial bolus of propofol 1mg/kg, with repeat boluses of 0.25mg/kg. Intervention group: Received an initial target effect-site concentration of 4mcg/ml, followed by maintenance target effect-site concentration of 2.5mcg/ml, titrated by 0.5mcg/ml from baseline infusion rate as needed. Oxygen saturation, blood pressure and heart rate were evaluated immediately before administering the sedative and at 2.50, 5.00, 7.50 and 10.00 minutes. Oxygen desaturation below 90% in both study groups was recorded. Sedation starting time, stopping time, waking up time and overall duration of time to recovery of participants in each study arm was recorded. RESULTS: More hypoxic episodes were observed in the intermittent bolus group with statistically significant association between control and the incidence of hypoxia: Chi square test, p=0.037. There were more hypotensive episodes in the TCI group but not achieving statistical significance: Chi square test for association X2(1) = 0.962, p=0.327.The time to recovery between the two groups was comparable, with 18.84 ± 10.76 minutes in the bolus group and 19.72 ± 9.27 minutes in the TCI group; no statistically significant difference was shown: Student's t-test, p=0.0564. CONCLUSION: TCI of propofol was associated with fewer episodes of hypoxia compared to intermittent bolus administration. Similar hemodynamic profiles and comparable time to recovery were demonstrated by these two sedation techniques.